2021
DOI: 10.1136/bmjgh-2021-005066
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of participatory women’s groups scaled up by the public health system to improve birth outcomes in Jharkhand, eastern India: a pragmatic cluster non-randomised controlled trial

Abstract: IntroductionThe WHO recommends community mobilisation with women’s groups practising participatory learning and action (PLA) to improve neonatal survival in high-mortality settings. This intervention has not been evaluated at scale with government frontline workers.MethodsWe did a pragmatic cluster non-randomised controlled trial of women’s groups practising PLA scaled up by government front-line workers in Jharkhand, eastern India. Groups prioritised maternal and newborn health problems, identified strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Preparation, planning and community sensitisation meetings and recruitment constituted less than 1% of total costs (Table 3 and Figures 2). FLAG's impact evaluation found that the intervention saved 188 neonatal lives over a two years period (min: 16 -max: 327), using lower and higher bound of confidence interval around impact) in the three early intervention districts taking part in the evaluation [19]. Over the 42 months of scale up, we estimated that the intervention saved a total 11,803 neonatal lives across 20 districts (min: 1026 -max: 20,527) [19].…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Preparation, planning and community sensitisation meetings and recruitment constituted less than 1% of total costs (Table 3 and Figures 2). FLAG's impact evaluation found that the intervention saved 188 neonatal lives over a two years period (min: 16 -max: 327), using lower and higher bound of confidence interval around impact) in the three early intervention districts taking part in the evaluation [19]. Over the 42 months of scale up, we estimated that the intervention saved a total 11,803 neonatal lives across 20 districts (min: 1026 -max: 20,527) [19].…”
Section: Resultsmentioning
confidence: 96%
“…FLAG’s impact evaluation found that the intervention saved 188 neonatal lives over a two years period (min: 16 – max: 327), using lower and higher bound of confidence interval around impact) in the three early intervention districts taking part in the evaluation[19]. Over the 42 months of scale up, we estimated that the intervention saved a total 11,803 neonatal lives across 20 districts (min: 1026 - max: 20,527) [19]. This translates to an estimated 363,621 (discounted) life years saved, with a range of 31,609 to 632,386 (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations